Food rules! : the stuff you munch, its crunch, its punch, and why you sometimes lose your lunch - Haduch, Bill.; Stromoski, Rick (New York : Dutton Children's Books, 2001)
A lighthearted look at how the digestive system works that also contains food facts such as what comprised the last meal on the "Titanic.".
Includes bibliographical references (p. 104) and index.
Booklist.
Science Books & Films (A.A.A.S.).
5.0
3-6
Keywords: Food -- Composition -- Juvenile literature; Food; Nutrition; Food; Nutrition; Food; Nutrition